Warsaw-Based “Erec Israel”: An Image of Palestine and Its Inhabitants in a Zionist Periodical from the Beginning of the Interwar Period - Ratajczyk, Maciej (Porównania, 2025)
“Erec Israel” was a Hebrew monthly published in Warsaw in 1919 by Organizacja Syjonistyczna w Polsce (The Zionist Organization of Poland). The aim of the article is to trace and understand the portrayal of Palestine as a place to which the target reader would emigrate in the future. An additional goal was to determine who this potential reader was. Much attention was paid to various Zionist narratives present in the periodical, such as the belief that Jewish migration was for the benefit of the local population. Furthermore, the Orientalizing of Palestinian Arabs was tackled. The information obtained from the study was contextualized through, for example, a reading of Altneuland by Theodor Herzl and The Innocents Abroad by Mark Twain. The author concluded that the “Erec Israel” focused on the economic image of Palestine and that the target readership was a representative of the middle class.